Antimicrobial susceptibility profiles of Escherichia coli isolates from domestic pigeons in Hungary - Kerek, Ádám; Szabó, Ábel; Jerzsele, Ákos (Frontiers in Veterinary Science, 2025)
BackgroundThis cross-sectional observational study aimed to determine the antimicrobial susceptibility profiles of Escherichia coli isolates from domestic pigeons (Columba livia domestica) in Hungary.MethodsA total of 134 non-redundant isolates were obtained from oropharyngeal and cloacal swabs collected across multiple geographic regions. Antimicrobial susceptibility testing was conducted using the microdilution method, following Clinical and Laboratory Standards Institute (CLSI) guidelines. Minimum inhibitory concentration (MIC) values were determined for a panel of antibiotics relevant to both veterinary and human medicine. Resistance patterns were analyzed using statistical tools including hierarchical clustering, network graph analysis, decision tree modeling, and Monte Carlo simulation.ResultsMultidrug-resistant (MDR) strains constituted 65.7% of the total, while extensive drug-resistant (XDR) and pan-drug-resistant (PDR) strains were found in 4.5% and 1.5% of isolates, respectively. The highest resistance rates were observed for neomycin (76.1%) and florfenicol (72.4%), whereas ceftriaxone and imipenem showed the lowest resistance rates (0.7% and 1.5%). Correlation analysis indicated notable associations between resistance to neomycin, doxycycline, and florfenicol, suggesting potential cross-resistance mechanisms. Monte Carlo simulation estimated an average MDR prevalence of 64.4% (95% CI: 50.0–77.6%). The high prevalence of antimicrobial resistance among pigeon-derived E. coli isolates underscores the potential public health risks posed by avian reservoirs within the One Health context.ConclusionsThese findings highlight the need for enhanced AMR surveillance and responsible antibiotic stewardship in veterinary settings. Further molecular investigations are warranted to elucidate the genetic basis of resistance in this population.